Dermotics. Classification and treatment of ten cases. - Andreoli, E.; Finore, E.D.; Provini, A.; Palermi, G.; Fiore, A.; Rovatti, G.; Mazzatenta, C.; Voglino, A.; Paradisi, M. (European Journal of Pediatric Dermatology, 2005)
Dermotics are defined as those repeated, compulsive movements, not always accessible by consciousness, causing several types of cutaneous damage. On the base of 10 particularly reported clinical cases, we discussed, from a psychosocial point of view, the importance of this so little explorated reality. We subdivided the clinical cases into five psychodiagnostic categories, a useful operation that can make the clinical comprehension of such behaviours easier and can estimate the usefulness of a cooperation between pediatrician, dermatologist and psychologist.